Trends in testing and prevalence of elevated Lp(a) among patients with aortic valve stenosis. (May 2022) - Bhatia, Harpreet S.; Ma, Gary S.; Taleb, Adam; Wilkinson, Michael; Kahn, Andrew M.; Cotter, Bruno; Yeang, Calvin; DeMaria, Anthony N.; Patel, Mitul P.; Mahmud, Ehtisham; Reeves, Ryan R.; Tsimikas, Sotirios
Abstract: Background and aims: Lipoprotein(a) [Lp(a)] is causally associated with aortic valve stenosis (AS) but Lp(a) testing among AS patients is not broadly incorporated into clinical practice. We evaluated trends in Lp(a) testing in an academic medical center. Methods: Educational efforts and adding Lp(a) to the lipid panel on the electronic medical record (EMR) and pre-procedure order sets were used to increase awareness of Lp(a) as a risk factor in AS. Medical records at University of California San Diego Health (UCSDH) were analyzed from 2010 to 2020 to define the yearly frequency of first time Lp(a) testing in patients with diagnosis codes for AS or undergoing transcatheter aortic valve replacement (TAVR). Results: Lp(a) testing for any indication increased over 5-fold from 2010 to 2020. A total of 3808 patients had a diagnosis of AS and 417 patients had TAVR. Lp(a) levels >30 mg/dL were present in 37% of AS and 35% of TAVR patients. The rates of Lp(a) testing in AS and TAVR were 14.0% and 65.7%, respectively. In AS, Lp(a) testing increased over time from 8.5% in 2010, peaking at 24.2% in 2017, and declining to 13.9% in 2020 ( p < 0.001 for trend). Following implementation of EMR order-sets in 2016, Lp(a) testing in TAVR cases increased to a peak of 88.5% in 2018. Conclusions: Elevated Lp(a) is prevalent in AS and TAVR patients. Implementation of educational efforts and practice pathways resulted in increased Lp(a) testing in patients with AS. This study represents a paradigm that may allow increased global awareness of Lp(a) as a risk factor for AS. Graphical abstract: Image 1 Highlights: Lp(a) is strongly related to aortic valve stenosis (AS) risk. Elevated Lp(a) is highly prevalent among AS patients. Lp(a) testing among AS patients has improved over time. Education and order sets can significantly increase Lp(a) testing.